Real-time pricing program in a smart grid environment. (April 2013) - Monsef, Hassan; Wu, Bin
Improving system efficiency and reliability is motivating countries to design and execute different types of time of use demand response programs. However, certain deficiencies prevent these programs from reaching their goals. Smart meters as a mechanism could help the electric system to reach the highest demand-side management goals which are inaccessible through today's methods. On the other hand, realization of smart meters in a system would be very costly. In this situation, identifying the most influential buses to implement the infrastructures of a smart grid is of highest importance. In this paper, after a short overview of demand response programs and problems facing them, a smart meter is introduced as a solution to these problems. As a test grid, the IEEE 57-bus network has been chosen to compare the results of the execution of a normal time of use program and real-time pricing program available in a smart grid. In order to execute the mentioned programs in this system, 10 buses have been selected as the most influential buses using a generation shift factor method. The execution of time of use and real-time pricing programs on the selected buses have been simulated using a demand response model. Finally, the time of use program and the real-time pricing program in a smart grid environment have been compared with respect to load shape modification, load factor, price curve, and 'Expected Power Not Supplied'.